A Study on the English Writing Teaching of TEM-4 Based on Pigai Platform - Liu, Lijie (Pacific International Journal, 2022)
As far as language acquisition is concerned, writing is a vital part of comprehensive language skills. In the traditional pedagogy of English writing, feedback from the teachers has always played a crucial role in the process. It is an effective way to improve students’ writing skill by receiving feedback and revising their writing based on it. However, as things stand now, it is hard for teachers to give timely and specific feedback to all of the students. With the advancement of technology, to apply automated writing evaluation system presents a new model in the teaching of English writing, capable of scoring quickly from more detailed aspects than teachers, thereby garnering tremendous attention in the academic circle. Nowadays, Pigai platform is one of the most widely used automatic evaluation systems in China. Hence, this study aims to investigate the effectiveness of Pigai platform with respect to the teaching of English writing for Test for English Majors Level 4 by taking two classes as the research subject. A contrastive study was conduced by employing questionnaire, interview and analysis of pre-test and post-test data. The results shows that the feedback from Pigai platform, compared with traditional feedback from teachers proves instrumental in effectively improving students’ writing proficiency, motivation and self-efficacy, so it is feasible to incorporate it into the teaching of English writing for TEM-4. In a word, the author hopes to contribute to the teaching and learning of English writing as well as the advancement of automated writing evaluation system.